Individual and Environmental Factors Associated with Pulmonary Tuberculosis: A Cross-Sectional Study in an Urban Community - Zahroh, Chilyatiz; Sudarianik, Sudarianik; Ainiyah, Nur; Setiyowati, Eppy; Soleha, Umdatus; Mulyadi, Mulyadi (Journal of Applied Nursing and Health, 2025)
Background: Tuberculosis is a contagious disease caused by the bacterium Mycobacterium tuberculosis. TB cases have increased at the Balongsari Health Center in recent years. The research aims to analyze individual and environmental factors related to pulmonary tuberculosis incidence at the center. Methods: This study applied the STROBE guidelines. It was an analytical observational study using a cross-sectional design. The study population comprised 152 tuberculosis (TB) patients and TB suspects registered at the Balongsari Health Center between January and December 2022. The sample consisted of pulmonary TB patients (TCM+) and TB suspects (TCM−) in a 1:1 ratio, selected through simple random sampling. The variables assessed included age, sex, HIV/AIDS status, diabetes mellitus, nutritional status, smoking history, lighting conditions, and housing occupancy density. Data were analyzed using the Chi-Square test. Results: The analysis showed that the factors significantly associated with the incidence of pulmonary tuberculosis at the Balongsari Health Center were age (p = 0.01), diabetes mellitus (p < 0.001), nutritional status (p < 0.001), smoking history (p < 0.001), and lighting conditions (p < 0.001). In contrast, gender (p = 0.15), HIV/AIDS status (p = 0.08), and occupancy density (p = 0.10) were not significantly associated with the incidence of pulmonary tuberculosis. Conclusion: Factors associated with the incidence of pulmonary tuberculosis included age, diabetes mellitus, smoking history, nutritional status, and lighting conditions. Conversely, gender, HIV infection, and occupancy density were not associated with pulmonary tuberculosis incidence.